Analisis Fonologi pada Dialek Sehari-hari Masyarakat Desa Adat Penglipuran Bali - Hendratno, Adityawan; Rizky, Alya; Kezia, Yohana; Fikri, Moh; Kirana, Citra Dewi; Sholihatin, Endang (Peneliti.net, 2025)
The article entitled